Calcium techniques : a laboratory manual - Parys, Jan B.; Bootman, Martin D.; Yule, David I.; Bultynck, Geert
"This laboratory manual provides step-by-step protocols for studying many facets of Ca2+ signaling, as well as background information on the principles and applications of the techniques. Contributors discuss how to use fluorescent, luminescent, and genetically encoded Ca2+ probes in conjunction with state-of-the-art imaging modalities to characterize Ca2+ signals. Electrophysiological measurements of Ca2+ channel activity are described, as are radioactive Ca2+ flux assays and methods to investigate signaling mediated by specific Ca2+-mobilizing messengers (IP3, cADPR, and NAADP). Techniques to modulate and suppress intra- and intercellular signals are also provided. Each protocol is complete with a list of required materials, detailed recipes for media and reagents, and troubleshooting advice"--
Fluorescence -- Luminescence -- Radioactive techniques -- Electrophysiology -- Special tissues -- NAD(P)-derived messengers -- Measuring and modeling Ca2+ dynamics.
Includes bibliographical references and index.
Keywords: Calcium -- Laboratory Manuals; Calcium Channels -- Laboratory Manuals; Calcium Signaling -- Laboratory Manuals; Fluorometry -- Laboratory Manuals